I love everybody (and other atrocious lies) eaudiobook True tales of a loudmouth girl. - Notaro, Laurie (Tantor Media, 2011)
Laurie Notaro is married, mortgaged, and now—miraculously—employed in the corporate world, discovering that bosses come in all shapes, sizes, and degrees of mental stability. After maxing out her last good credit card at Banana Republic, she's dressed for success and ready to face the jungle: surviving feral, six-foot-plus Gretchen ("The Three Thousand Faces of Eve") before battling the overbearing, overstuffed (in way -too-small pants) new mom Suzi, who ruthlessly cancels Laurie's newspaper column and learns that payback can be a bitch. Laurie also explores the backstabbing world of preschoolers at a Halloween party, the X-rated madness of a family trip to Disneyland, and the pressure from her QVC-addicted mother and the rest of the world to reproduce. But while losing more friends to babies than to booze, she realizes there's a plus side: for at least a couple of months, she gets to be the thinner friend. I Love Everybody (and Other Atrocious Lies) is Notaro at her deliciously quirky best. Can a woman prone to what her loved ones might term "meltdowns" (she considers them "Opportunities to Enlighten") put a smile on her face and love everybody? Take a guess.